Analisis Tingkat Stres Akademik Pada Mahasiswa Selama Pembelajaran Jarak Jauh Dimasa Covid-19 - Ade Chita Putri Harahap; Dinda Permatasari Harahap; Samsul Rivai Harahap (Program Studi Bimbingan dan Konseling FKIP UMSU, 2020)
The variety of stressors in lectures online for a pandemic COVID-19 as an internet connection is not tasty, complete the task that much in a short time, to respond to instructions quickly, as well as the need to adapt rapidly to the situation of learning from home is a condition that can cause stress on students. Ideally, the learning process carried out remotely can enhance the learning process. This change will certainly not be easy for students, including students. This study aims to determine the level of academic stress on students. This research uses a descriptive quantitative approach. The sample of this research is 300 students. Data were analyzed using descriptive formulas. Data collection is done using a Likert type scale that has been tested for validity and reliability. Based on data analysis, the results show that, on average, students experience stress in the medium category.